The 1st all african post harvest congress & exhibition (2014)
Stored product insect pests cause significant losses in maize in sub-Saharan Africa (SSA). Several-risks technologies are available for use as alternatives to convention insecticides in SSA, In the present study, conducted february -December 2016,efficacy of piper guineense, Bularafa diatomaceous earth (DE) PICS bags, ZeroFly bags and permethrin (Rambo) to preserve maize quality in nigerian market was assessed. A sixth treated was negative control comprising maize in untreated polypropylene bags, study locations were in four markets in ibadan. Oyo and ilorin towns, Each market had a storehouse (SH) which contained experimmental 100kg bags, in each SH each treatment had six bags were destructively sampled every four months, PICS bags were the most effective and had infestation levels of 0.54 live insects per kg of maize, infestation levels in the control were <53.15 psocide were prevalent during rainy season withb highest levels of 14.71 in the ZeroFly treatment in october. The facts that the highest infestation levels (53.15) were found in the control indicates the importance of insect pest management in SH. Based on data obtained, order of effectiveness of the treatment was PICS > bags ZeroFly bags, DE and P. guineense, which are reduced -risk measures for insect control can be incorporated in integrated management of stored product insect pest in SHs.